1998
DOI: 10.1159/000046297
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Calcium Nephrolithiasis

Abstract: Calcium nephrolithiasis (CaNL) accounts for more than 70% of all renal stones, and its prevalence has increased in the last decades. Under this definition are included patients passing stones, composed of calcium oxalates and/or calcium phosphates. Current views of the pathogenesis of CaNL are based on the role of metabolic abnormalities which concur to render urines more conducive to crystallization. Therefore, the diagnostic approach is aimed at detecting these abnormalities, and the medical treatment assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…However, previously it was reported that glucocorticoids may increase the risk of kidney stones [10]. Glucocorticoid–dependent nephrolithiasis (GDNL) may result as a consequence of hypercalciuria, hyperuricosuria, and hypercystinuria, which are common features of patients with Cushing's syndrome [2022] and are clearly associated with kidney stones formation [23]. However, GDNL probably has a multifactorial pathogenesis, because several other factors related with glucocorticoid excess such as obesity, hypertension, insulin resistance may contribute to kidney stones formation [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, previously it was reported that glucocorticoids may increase the risk of kidney stones [10]. Glucocorticoid–dependent nephrolithiasis (GDNL) may result as a consequence of hypercalciuria, hyperuricosuria, and hypercystinuria, which are common features of patients with Cushing's syndrome [2022] and are clearly associated with kidney stones formation [23]. However, GDNL probably has a multifactorial pathogenesis, because several other factors related with glucocorticoid excess such as obesity, hypertension, insulin resistance may contribute to kidney stones formation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this population must be closely followed and, even after this first episode, be evaluated with a complete metabolic study because the rule is recurrence [8,9]. Some authors defend that metabolic study and analysis of stone are important for determining different profiles of lithogenic risk, which allows for adequate treatment to be based on risk [10].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the experimental and clinical studies on calcium oxalate urolithiasis performed during the last two decades [1,[4][5][6][7][8][12][13][14][15][16][17] has been used to elaborate new step-by-step approaches for diagnosing and treating this frequent disorder. These clinic and laboratory research have included the quantitative mineralogical analysis of calculi by X-ray diffraction or IR-spectroscopy, electronic microscopy study of their texture and biochemical analysis of blood and urine of patients with COH renal stones.…”
Section: Methodsmentioning
confidence: 99%
“…There are many excellent studies on calcium oxalate urolithiasis that have been performed for the last twenty years (see, for example [4][5][6][7][8][12][13][14][15][16][17] and references therein). These results can provide at least, as a first approximation, the relationship between metabolic disorders that caused COH stone formation and the stone composition.…”
Section: Introductionmentioning
confidence: 99%